2018
DOI: 10.3389/fendo.2018.00350
|View full text |Cite
|
Sign up to set email alerts
|

Ulipristal Acetate Interferes With Actin Remodeling Induced by 17β-Estradiol and Progesterone in Human Endometrial Stromal Cells

Abstract: Ulipristal acetate (UPA) is a selective progesterone receptor modulator (SPRM) used for emergency contraception and for the medical management of symptomatic uterine fibroids (UF). Treatment with UPA turns in amenorrhea and UF volume reduction. Treatment with UPA is associated with the frequent development of benign, transitory endometrial changes known as SPRM-associated endometrial changes (PAECs). Why PAECs develop and their biological or cellular basis is unknown. Sex steroids, including estrogen and proge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…Consistent with studies in European and Japanese women 17 , 22 and the known mechanism of action of UPA, 23 , 24 the nonphysiological changes that occurred at the endometrium during treatment with SPRMs were temporary and benign. Mean endometrial thickness was not different from baseline levels by the end of the study.…”
Section: Discussionsupporting
confidence: 80%
“…Consistent with studies in European and Japanese women 17 , 22 and the known mechanism of action of UPA, 23 , 24 the nonphysiological changes that occurred at the endometrium during treatment with SPRMs were temporary and benign. Mean endometrial thickness was not different from baseline levels by the end of the study.…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, both of them are directly involved in regulating oocyte meiosis, because TZP contraction would lead to failure of cGMP transport from somatic cells to oocytes. Studies have shown that estrogen is a regulator of the actin skeleton in various cells, and estrogen regulates actin cytoskeletal reorganization via different molecular mechanisms and signaling pathways (Giretti et al, 2014;Kramar et al, 2009;Shortrede et al, 2018;Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, both of them are directly involved in regulating oocyte meiosis, because TZP contraction would lead to failure of cGMP transport from somatic cells to oocytes. Studies have shown that estrogen is a regulator of the actin skeleton in various cells, and estrogen regulates actin cytoskeletal reorganization via different molecular mechanisms and signaling pathways (Giretti et al, 2014; Kramar et al, 2009; Shortrede et al, 2018; Wang et al, 2020). ERK1/2 is a serine/threonine protein kinase involved in the regulation of a variety of biological processes, including cell adhesion, cell cycle progression, cell migration, cell survival, differentiation, metabolism, and proliferation (Roskoski, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…UPA interferes with estradiol and progesterone actions in ESC by decreasing actin cytoskeleton rearrangement, focal adhesion formation, and reducing FAK and Moesin phosphorylation/activation. This leads to an alteration of cell morphology and to the inhibition of cell motility 58 . The above discussion lets us understand that the main MOA of ellaOne ® is its anti-implantation effect on the endometrium, whenever it is taken in the menstrual cycle.…”
Section: Ellaone ® and Endometriummentioning
confidence: 99%